2010
DOI: 10.1007/s00464-010-1036-8
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized, controlled trial comparing lightweight versus heavyweight mesh in chronic pain incidence after TEP repair of bilateral inguinal hernia

Abstract: Lightweight polypropylene mesh may be preferable to heavyweight mesh for TEP inguinal hernia repair because it provides less postoperative foreign body sensation; however, there was no significant difference in the incidence of chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…The results were controversial and limited; only four of the laparoscopic surgery studies [82][83][84][85] had a follow-up longer than 3 months.…”
Section: Selection Of Mesh Materialsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results were controversial and limited; only four of the laparoscopic surgery studies [82][83][84][85] had a follow-up longer than 3 months.…”
Section: Selection Of Mesh Materialsmentioning
confidence: 96%
“…One meta-analysis [68] and 17 RCTs have been published comparing heavyweight meshes to lightweight meshes, with nine of the studies using open surgery [69][70][71][72][73][74][75][76][77] and eight using laparoscopic repair [78][79][80][81][82][83][84][85]. The results were controversial and limited; only four of the laparoscopic surgery studies [82][83][84][85] had a follow-up longer than 3 months.…”
Section: Selection Of Mesh Materialsmentioning
confidence: 96%
“…There are reports that reduced tensile strength has a negative impact on the hernia recurrence and migration rate [11]. Studies were published that link the use of light-weight prostheses with reduced male fertility and increased peritoneal adhesions after operation [12].…”
Section: Polypropylene Implantsmentioning
confidence: 99%
“…Previously published studies concluded that lightweight, large-pore and monofilament meshes possess the best biocompatibility for hernia repair by inducing a lower rate of chronic inflammatory reaction and hence less postoperative pain, less seroma formation and foreign body sensation [33][34][35][36]. In view of the excellent in vitro characteristics observed in light-weight polypropylene meshes [8,12,32], we investigated the biocompatibility of the new Optilene® LP mesh in an established animal model [8].…”
Section: Discussionmentioning
confidence: 99%